2016
DOI: 10.1063/1.4966153
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Green-Kubo approach to the average swim speed in active Brownian systems

Abstract: We develop an exact Green-Kubo formula relating nonequilibrium averages in systems of interacting active Brownian particles to equilibrium time-correlation functions. The method is applied to calculate the density-dependent average swim speed, which is a key quantity entering coarse grained theories of active matter. The average swim speed is determined by integrating the equilibrium autocorrelation function of the interaction force acting on a tagged particle. Analytical results are validated using Brownian d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
56
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 22 publications
(57 reference statements)
9
56
0
Order By: Relevance
“…In Ref. [74,78], a similar linear dependence of v(ρ) on ρ was found for a system of ABPs in three spatial dimensions. Reference [79] considers a system of reproducing bacteria and uses the function v(ρ) = v 0 e −cρρ for the densitydependent swimming speed.…”
Section: A Density-dependent Swimming Speedsupporting
confidence: 67%
“…In Ref. [74,78], a similar linear dependence of v(ρ) on ρ was found for a system of ABPs in three spatial dimensions. Reference [79] considers a system of reproducing bacteria and uses the function v(ρ) = v 0 e −cρρ for the densitydependent swimming speed.…”
Section: A Density-dependent Swimming Speedsupporting
confidence: 67%
“…We have demonstrated that the average swim speed, which describes how the motion of each particle is obstructed by its neighbors, can be obtained from a history integral over the equilibrium autocorrelation of tagged-particle force fluctuations [3]. The theory was tested using active Brownian dynamics simulations and provides a solid basis for the development of first-principles theoretical approaches.…”
Section: Introductionmentioning
confidence: 99%
“…ABP has been characterized in terms of thermodynamic quantities such as pressure and chemical potential [28][29][30][31][32][33] and its phase behaviour analysed in great detail [34][35][36][37][38][39]. Several recent works have studied its linear response (and of similar active particles modelled in terms of an Ornstein-Uhlenbeck process) from different viewpoints: (i) introducing an effective temperature characterizing FDT violations [40][41][42][43] ; (ii) taking equilibrium as the reference state and considering activity as a perturbation of it [24,25,44]; (iii) deriving expressions of linear response functions in terms of weighted averages over the unperturbed dynamics [43,45,46], in the same spirit as the Malliavin weights sampling [47]. In the present letter, we first characterize the violations of the FDT in ABP, showing how the non-equilibrium character of activity comes into play in an extended FDT that we establish, and then derive Green-Kubo expressions for its transport coefficients in terms of its non-equilibrium fluctuations.…”
mentioning
confidence: 99%